Pendidikan Kewirausahaan Untuk Anak Usia Dini - Saiful Arif; Izzatul Luthfiah Rahman; Dias Intan Sholatiah; Irma Suryandari; Ludi Wishnu Wardana; Bagus Shandy Narmaditya (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study explores the influence of social entrepreneurship education in the context of preschool education and its impact on children's development. Along with the increasing awareness of social entrepreneurship, various social entrepreneurship activities have been implemented to support social welfare and community sustainability. Social entrepreneurship education plays a role in improving individuals' ability to identify and address social problems with innovative solutions, while developing independence, creativity, empathy, and rational thinking skills. This study also highlights the importance of integrating social entrepreneurship education at the preschool education stage, as it can strengthen children's self-esteem development and form innovative perspectives that are beneficial in the long term. By involving social entrepreneurship education from an early age, it is expected to prepare children to become individuals who are sensitive to social and environmental issues, and are able to contribute positively to society. These findings confirm that the integration of social entrepreneurship in preschool education has the potential to enrich children's social, cognitive, physical, linguistic, and emotional development.